Profile and Differences in Anthropometric Data and Jumping Ability Performance between Elite and Amateur U16 Volleyball Players - Gaetano Altavilla; Giovanni Esposito; Rosario Ceruso; Felice Di Domenico; Tiziana D'Isanto (OVS LLC, 2022)
Research purpose. The purpose of this study is to verify if there are significant differences between different anthropometric and jumping ability variables by testing two groups of elite and amateur volleyball players (under 16) after having submitted the two groups to the same training protocol performed 4 times a week for 4 months. Materials and methods. The study was carried out on 24 volleyball players divided into two groups. The following anthropometric and jumping ability parameters were assessed in all subjects: height, weight, body mass index, height with a stretched arm and height with two extended arms. The jumping ability measurement was carried out with the Vertec jump test. Results. The results of the anthropometric parameters showed significant differences between the two groups on all the variables considered:  in height (p = 0.00), in weight (p = 0.00), in Vertec attack with a stretched arm, AH1 (p = 0.00) and in Vertec wall with two outstretched arms, AH2 (p = 0.01). The results of the jumping ability parameters showed significant differences between the two groups (elite and amateur):  in Vertec Wall, VW (p = 0.00) and Vertec Attack with run-up, VA (p = 0.00); and a high correlation was shown for both the groups. Conclusions. Above all, in high-level youth volleyball, the anthropometric and jumping ability profile is directly linked to the evaluation; training and continuous monitoring of physical qualities and jumping ability become an important aspect for the control of performance and the possibility of selecting talented players.